Separability of active semantic and phonological maintenance in verbal working memory - Nishiyama, Ryoji (PLoS One, 2018)
Models of verbal working memory that incorporate active memory maintenance, long-term memory networks, and attention control have been developed. Current studies suggest that semantic representations of words, evoked via long-term memory networks, are actively maintained until they are needed to fulfill a role. In other words, it is possible that some mechanism actively refreshes semantic representations of words, analogous to but independently from articulatory rehearsal which refreshes phonological representations. One valuable piece of evidence is a double dissociation, observed in a dual task paradigm in which manual tapping disrupted a semantic memory task while articulatory suppression disrupted a phonological memory task. However, in that study, the secondary tasks could have competed not only with the maintenance but also with the encoding activities. Additionally, the study items in the phonological memory tasks were words; hence, the discriminability of the memory tasks is doubtful. The present study, therefore, examined a potential double dissociation in situations where the secondary tasks could not compete with encoding, using a modified phonological memory task. Furthermore, this article discusses a potential mechanism for maintaining semantic representations.